Mask Dance training's effect on children's confidence - Apriliyani, Dwi (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
Self-Confidence is an attitude in every individual who feels confident in his ability to act and is not easily influenced by others. People with self-confidence are optimistic, able to make their own decisions, and desire to achieve more. This program aimed to determine how to increase students' self-confidence through Mask Dance training at UPTD SD Negeri 2 Cantigi Kulon because self-confidence is a character value that students must have, especially in dancing. Data was collected using class action research, observation, and documentation methods. The students' confidence can be seen when students do not feel embarrassed when dancing in front of a crowd. This program aims to train children's mentality through Mask Dance activities for students in grades three to five. This program describes that students' self-confidence increases through memorizing dance moves and giving encouragement or motivation from the coach.